1992
DOI: 10.1007/bf00197044
|View full text |Cite
|
Sign up to set email alerts
|

Decreased ribulose-1,5-bisphosphate carboxylase-oxygenase in transgenic tobacco transformed with ?antisense? rbcS

Abstract: The effect of nitrogen supply during growth on the contribution of ribulose-1,5-bisphosphate carboxylase-oxygenase (Rubisco; EC 4.1.1.39) to the control of photosynthesis was examined in tobacco (Nicotiana tabacum L.). Transgenic plants transformed with antisense rbcS to produce a series of plants with a progressive decrease in the amount of Rubisco were used to allow the calculation of the flux-control coefficient of Rubisco for photosynthesis (CR). Several points emerged from the data: (i) The strength of Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
82
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(97 citation statements)
references
References 123 publications
13
82
0
2
Order By: Relevance
“…Therefore, it was assumed that the carboxylation is the rate limiting step (Hartmann and Harpel, 1994). Although this view has been revisited because the overexpression of Rubisco did not increase the carboxylation efficiency in transgenic plants (Quick et al, 1992) it is obvious that the carbon flux through the Calvin cycle is far too low compared to the absorption capacity of the plants. A rough estimate from the rate constants and the stoichiometry of the cytochrome f, which is involved in the rate limiting step of the ETR chain (Wilhelm and Wild, 1984), and the RubisCo (as a representative of the whole Calvin cycle) shows that the ETR is potentially up to 10 times high (Raines, 2003).…”
mentioning
confidence: 99%
“…Therefore, it was assumed that the carboxylation is the rate limiting step (Hartmann and Harpel, 1994). Although this view has been revisited because the overexpression of Rubisco did not increase the carboxylation efficiency in transgenic plants (Quick et al, 1992) it is obvious that the carbon flux through the Calvin cycle is far too low compared to the absorption capacity of the plants. A rough estimate from the rate constants and the stoichiometry of the cytochrome f, which is involved in the rate limiting step of the ETR chain (Wilhelm and Wild, 1984), and the RubisCo (as a representative of the whole Calvin cycle) shows that the ETR is potentially up to 10 times high (Raines, 2003).…”
mentioning
confidence: 99%
“…The antisense mutants have been used for a wide variety of molecular, bio chemical and physiological studies to examine the mechanisms that regulate Rubisco biosynthesis, and to investigate the control that Rubisco exerts on photosynthesis, plant growth and development (reviewed by Stitt and Schulze, 1994;Rodermel, 1999 Investigations of pigment composition and content in the antisense mutants have focused on chlorophyll. These studies revealed that chloro phyll levels are reduced in plants with very low amounts of Rubisco, but that Chi a/C hi b ratios are only weakly affected in these plants (Quick et al, 1991(Quick et al, , 1992; Jiang and Rodermel, 1995). While this suggests that the composition of the thylakoid membrane is relatively refractory to changes in Rubisco content, chlorophyll fluorescence and flu orescence quenching measurements demonstrated that photosynthesis is inhibited in the antisense plants, especially in mutants with sharp reductions in Rubisco (Quick et al, 1991;1992;Stitt et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that chloro phyll levels are reduced in plants with very low amounts of Rubisco, but that Chi a/C hi b ratios are only weakly affected in these plants (Quick et al, 1991(Quick et al, , 1992; Jiang and Rodermel, 1995). While this suggests that the composition of the thylakoid membrane is relatively refractory to changes in Rubisco content, chlorophyll fluorescence and flu orescence quenching measurements demonstrated that photosynthesis is inhibited in the antisense plants, especially in mutants with sharp reductions in Rubisco (Quick et al, 1991;1992;Stitt et al, 1991). These experiments further showed that the mutants are photoinhibited at lower light inten sities than in the wild-type (WT), although the precise mechanisms were not investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models are a useful tool for identifying these targets (Zhu et al, 2007;von Caemmerer, 2013). Based on studies of steady-state models of photosynthesis, as well as experimental work, several targets for improvement of photosynthesis have been postulated, including the introduction of CO2 concentrating mechanisms in C3 plants (von Caemmerer et al, 2012), increasing concentrations of SBPase (Zhu et al, 2007;Rosenthal et al, 2011) or Rubisco (Quick et al, 1992;Makino, 2003), bypassing photorespiration (Kebeish et al, 2007;von Caemmerer et al, 2012), increasing mesophyll conductance (Flexas et al, 2013), improving Rubsico kinetic properties (Whitney et al, 2001), or redistribution of chlorophyll within the canopy . However, given that different photosynthetic processes may also limit CO2 assimilation under fluctuating irradiance, additional targets can be identified that could contribute to further improvements of biomass production under natural conditions.…”
Section: What Are Potential Targets For Improvement Of Photosynthesismentioning
confidence: 99%